A 31P-NMR study of muscle exercise metabolism in mdx mice: evidence for abnormal pH regulation. - Dunn, J; Tracey, I; Radda, G (1992)
We have studied exercise metabolism in vivo in the mdx mouse model of Duchenne muscular dystrophy with 31P-nuclear magnetic resonance spectroscopy. Intracellular pH, ratios of phosphocreatine (PCr) to ATP and PCr to inorganic phosphate (P(i)) expressed as PCr/ATP and PCr/(PCr+P(i)) as well as tension generated at the Achilles tendon were measured during sciatic nerve stimulation. Tension was similar between the mdx and control strain C57Bl/10ScSn at 10 Hz stimulation but slightly higher than the control at 100 Hz. The PCr/ATP and PCr/(PCr+P(i)) ratios were significantly reduced in mdx vs. control muscle during exercise. Although resting muscle pH in mdx mice is more alkaline than normal muscle, the pH of mdx muscle during exercise is reduced relative to controls, as is the rate of pH recovery. Total lactate is not elevated in the cells and so it is argued that there is a reduction in the capacity to export proton equivalents in muscles of mdx mice which could be caused by an elevation in intracellular sodium. This provides more evidence of impaired ionic regulation in dystrophic muscle and could be used as an index for the evaluation in vivo of therapeutic interventions such as myoblast transfer or gene replacement therapy.